A study of the records management practices of the University of the Philippines - Office of the Student Regent - Peoro, Rolly Francis; Rey, Emma M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
As an office mandated by the UP students, the UP Office of the Student Regent (OSR) is responsible for an effective and transparent representation of the whole UP student body. With the important role being played by the OSR, transactions are being done in fulfillment of its functions and subsequently records are created as evidence of these transactions. These records which are administrative, fiscal, legal value to the OSR are also historically significant to the history of student activism of the UP student body.
Cognizant of the importance of the role being played by the OSR and its records, this study focused on its records management practices and provided a description of the records management practices of the OSR and recommendations for the improvement of its record management. The study focused on the following phases of records management of the Office of the Student Regent: records creation, records maintenance and control, records protection and preservation, storage and retrieval and records disposition and retention. The study used the descriptive method of research. Ocular inspection, interviews and observation were utilized to determine the present record management practices of the OSR. The result of the inspection, interviews and observation was then compared with the standards of record management.
The study found out that the UP OSR is facing some important issues regarding its records management. The office has no clear and strict policy regarding records creation, storage and retrieval, records maintenance and control, and records disposition and retention. The absence of strict and comprehensive policy produces problems on the UP OSR's records management such as loss of records, problem on space and equipment, and difficulty of retrieval of records.
Recommendations included training of staff, procurement of equipment, inventory and indexing, centralization of authority on access of records, and improvement of records retention and disposition.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Office of the Student Regent; Records -- Management